Cemeteries and the Environment: Analysis of a vertical cemetery in the Metropolitan Region of São Paulo - Iezzi, Amanda Alves; Júnior, Cláudio Barbosa Ferreira; Martins, Larissa Fernanda Vieira (Seven Editora, 2024)
Due to the growing concern about the impacts caused by cemeteries, this study aims to present and analyze the characteristics of vertical cemeteries, through a case study conducted in a vertical cemetery located in the Metropolitan Region of São Paulo (MRSP). Information about the project was collected through a questionnaire conducted with the operations supervisor. The project was built in a Permanent Preservation Area. Since the cemetery was implemented prior to CONAMA Resolution 335 of 2003, it was exempted from the installation license. It is found that all by-products generated in the processes of human body decomposition are treated, not generating impacts on air, water, and soil; the waste generated in daily activities also receives proper disposal. It is noted that, despite the need for adjustments regarding space occupation, such as the restoration of riparian vegetation, the vertical cemetery presents itself as an excellent alternative to reduce the spaces allocated to graves, making much better use of the location, besides solving the problem of overcrowding in necropolises, it also generates fewer impacts on the environment,  as the corpses are placed in drawers and thus do not come into contact with the soil, and there is no risk of the main contaminant, necrochorume, contaminating the soil and groundwater. DOI:https://doi.org/10.56238/sevened2024.010-060